SASMITA GENDHING: Dulu dan Kini. - Harti, Sri (Acintya, 2020)
ABSTRACTSasmita gendhing is a series of words that lead to the name gendhing-gendhing as a supporter of the wayang kulit purwa show. While the wayang kulit show format still refers to the format of last night's show with the genre of palace performance, the gendhing grade became a bridge between the mastermind and the singer to sound the gendhing as a support for certain scenes. In the development of the existence of gendhing-gendhing grades are slowly declining, even the majority of masterminds no longer use gendhing grades. The text-context approach from HeddyShri Ahimsa is used to reveal the variety of gendhing grades and to find the cause of the decline in the use of gendhing grades. The study conducted found various forms of gendhing grades, among them, are figurative words, wangsalan, and cangkriman. While the cause of the decline in the use of gendhing grades is noted due to the change of image, freedom of scene structure, freedom of choice of play, and cross-style performance. Keywords: gendhing grades, text-context, performance ABSTRAKSasmita gendhing merupakan rangkaian kata yang mengarah pada nama gendhing-gendhing sebagai pendukung pertunjukan wayang kulit purwa. Ketika format pertunjukan wayang kulit masih mengacu pada format pertunjukan semalam dengan genre pakeliran istana, sasmita gendhing menjadi jembatan antara dalang dengan pengrawit untuk membunyikan gendhing sebagai pendukung adegan tertentu. Dalam perkembangannya eksistensi sasmita gendhing- gendhing perlahan surut, bahkan mayoritas dalang tidak lagi menggunakan sasmita gendhing. Pendekatan teks-konteks dari HeddyShri Ahimsa digunakan untuk mengungkap ragam sasmita gendhing serta mencari penyebab surutnya penggunaan sasmita gendhing. Dari kajian yang dilakukan ditemukan beragam bentuk sasmita gendhing, di antaranya adalah kata kiasan, wangsalan, dan cangkriman. Sedangkan penyebab surutnya penggunaan sasmita gendhing ditengarai karena adanya perubahan citra, kebebasan struktur adegan, kebebasan pemilihan lakon, dan silang gaya pakeliran. Kata kunci: sasmita gendhing, teks-konteks, pakeliran